Kombucha Bacterial Cellulose Synthesized by Liquid Fermentation on Black Tea (Camellia sinensis): Effect of the Sucrose - Huerta, Natanael Victoriano; Iniesta, Salvador Alcántara; Cruz, Blanca Susana Soto; Morán, Placido Zaca; Díaz, Abdu Orduña; Lozano, Leslie Susana Arcila; Lopez, Marlon Rojas (European Journal of Applied Sciences, 2022)
Bacterial cellulose membranes were synthesized by liquid fermentation of the Kombucha strain into black tea (Camellia sinensis) at different concentrations of sucrose. Structural properties of bacterial cellulose Kombucha, such as lateral order index (LOI), total crystallinity index (TCI), hydrogen bond intensity (HBI), fraction (fa), as well as their dependence on sucrose content were evaluated by Fourier transform infrared spectroscopy, using different absorption bands of the vibrational spectrum. It was thus observed that sucrose tends to crystallize bacterial cellulose, due to the increase in the total index of crystallinity and lateral order, as well as the fraction (fa), while the index of hydrogen bonds decreased. The addition of organic cocoa (Theobroma cacao) in the culture medium prior to fermentation produced membranes with properties very similar to those prepared only with black tea. Obtaining type I cellulose and crystallization controlled by this process could contribute to obtaining high crystallinity membranes for biomedical and bioelectronic applications.